Application of Character Education Values in Citizenship Education Courses - Jainabu Sely; Fatimah Sialana; Titus Gaite (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Character education is lifelong education, as a process towards a perfect human being. Value is something abstract and ideal. application of Character Values in Citizenship Education courses to students, because universities have an important role in the process of strengthening character in the souls and individuals of the younger generation on campus. The research method used in this research is descriptive qualitative. A qualitative approach is an approach that aims to describe what is currently in effect by examining the relationship between the implementation of Pancasila values in strengthening national character and data analysis techniques carried out using interactive model data analysis techniques which have three stages, namely data reduction, data presentation. and conclusion. This research was conducted at the Pancasila and Citizenship Education Study Program, Fkip Unpatti. The formulation of the problem in this study is: 1. application of character values through citizenship education courses for even semester students. 2. the obstacles experienced in applying character values to even semester students in the Citizenship Education course. The objectives of this research are 1. application of character values through citizenship education courses for even semester students. 2. the obstacles experienced in applying character values to even semester students in the Citizenship Education course. The results of this study indicate that the application of character education to even semester students of the 2021 class requires character education to shape traits or behaviors that are not in accordance with Pancasila values, so with this the aim of character education is to form a good human person, a good society and good citizens in accordance with Pancasila values. The obstacles experienced in applying character values are related to the obstacles in students in applying character values in Citizenship Education courses that there are no obstacles encountered in citizenship education courses in the recovery process.